Statistical analysis of postural stability during gait for adults between normal and simulated abnormal gaits - Wong, Xing Hui; Sakeran, Hamzah; Salleh, Ahmad Faizal; Salim, Mohammad Shahril; Muhamad, Wan Zuki Azman Wan; Shapie, Mohamad Azlan Mohamed (AIP conference proceedings, 2023)
Walking is a common but complex daily activity for human. Walking is done when one leg is elevated and moved forward by flexing the hips and knee. Walking involves association of central nervous system, motor and sensory system. It has been previously shown that disrupted neural communication and musculoskeletal constraints may impair postural control and stability during gait and increase fall risk. Previous research have reported that distance between centre of pressure (COP) and centre of mass (COM) are suitable to study postural stability of patients that is affected by HSP disease. There is no research studied about normal and four types of simulated abnormal gaits which include hemiplegic, diplegic, bilaterally asymmetry and hunchback by analysing COP and COM. Fifteen male subjects and fifteen female subjects were involved in this research. Performances of subjects were captured with QTM system and analysed by Visual 3D software. For females, there was a significant difference in normal and hemiplegic gait in AP direction. For males, normal, hemiplegic and bilaterally asymmetry showed significant differences in AP direction while normal and diplegic demonstrated significant difference in ML direction. This finding concluded that COP-COM method can be suggested for clinical research and rehabilitation purpose.